2017
DOI: 10.2147/jpr.s138361
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Modic changes in cervical kyphosis and their association with axial neck pain

Abstract: BackgroundThe purpose of this study was to evaluate characteristics of Modic changes in cervical kyphosis (CK) and their association with axial neck pain.MethodsStudy participants included 286 asymptomatic or symptomatic patients with CK (mean age = 54.2 ± 12.2 years) who were consecutively enrolled from March 2009 to October 2015. Clinical and radiographic evaluations were performed at a university outpatient department. CK was classified as global type, reverse sigmoid type, or sigmoid type.ResultsThere were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Three studies reported other cervical spine MRI findings. One study reported greater mean spinal cord compression grade in chronic NSNP compared with controls. Myran et al found no difference in frequency of alar ligament high signal changes.…”
Section: Chronic Nonspecific Neck Painmentioning
confidence: 99%
“…Three studies reported other cervical spine MRI findings. One study reported greater mean spinal cord compression grade in chronic NSNP compared with controls. Myran et al found no difference in frequency of alar ligament high signal changes.…”
Section: Chronic Nonspecific Neck Painmentioning
confidence: 99%
“…None of the included studies identified differences in axial neck pain severity based on the presence or absence of Modic changes. However, five studies demonstrated an association with the presence of pain, 22,27 persistence of pain, 49 or symptom duration. 28,45 Clinically, this may indicate that patients with Modic changes present similarly to other patients with neck pain, but they may have experienced a prolonged disease course.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, MCs in the cervical vertebrae occur between 5% and 40% and positively correlate with the prevalence of neck pain and DD [14][15][16]. Hayashi et al have shown that patients with MCs were more likely to have severe DD at the same segment level (OR, 3.9; 95% confidence interval, 2.42-6.3) compared with those without MC [8].…”
Section: Discussionmentioning
confidence: 99%